Overexpression of polyphosphate kinase gene (ppk) increases bioinsecticide production by Bacillus thuringiensis - Doruk, Tugrul; Avican, Ummehan; Camci, Irem Yalim; Gedik, Sedef Tunca (Elsevier Gmbh, Urban & Fischer Verlag, 2013)
Polyphosphate (polyP), synthesized by polyp kinase (PPK) using the terminal phosphate of ATP as substrate, performs important functions in every living cell. The present work reports on the relationship between polyp metabolism and bioinsecticide production in Bacillus thuringiensis subsp. israelensis (Bti). The ppk gene of Bti was cloned into vector pHT315 and the effect of its overexpression on endotoxin production was determined. Endotoxin production by the recombinant strain was found to be consistently higher than that by the wild type strain and the strain that carried the empty plasmid. The toxicity of the recombinant mutant strain (LC50 5.8 +/- 0.6 ng ml(-1)) against late 2nd instar Culex quinquefasciatus was about 7.7 times higher than that of Bti (LC50 44.9 +/- 7 ng ml(-1)). To our knowledge this is the first reported study which relates polyp metabolism with bioinsecticide biosynthesis. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Polyphosphate kinase; ppk; Bacillus thuringiensis; Endotoxin; Bioinsecticide